2016
DOI: 10.1063/1.4971273
|View full text |Cite
|
Sign up to set email alerts
|

Thin film zinc oxide gas sensor fabricated using near-field electrospray

Abstract: Near-field electrospray was used to deposit zinc acetate precursor particles over comb electrodes. These particles were heated and oxidized to form a zinc oxide (ZnO) semiconductor at 500 °C. The resulting ZnO thin film on the comb electrode was incorporated into a gas sensor, which was examined using a custom built measurement system. The current that was measured through the electrodes was used to calculate the resistance of the ZnO between the fingers of the comb electrode. The resistance decreased as the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“… 14 For instance, Li et al 15 observed a strong visible emission peak centered at about 609 nm in ZnO nanorods (15 nm in diameter) as a result of large quantities of defects, thus enabled the high ethanol response by the total surface depletion. Different morphologies of ZnO nanostructures such as thin films, 16 nanorods, 17 nanowires, 18 and nanoparticles 19 have been also investigated for gas sensor applications. In our previous study, 20 the gas sensing properties of ZnO nanorods, nanowires, and nanoparticles were systematically compared, where the nanoparticles exhibited higher ethanol sensitivity because of their smaller crystal size.…”
Section: Introductionmentioning
confidence: 99%
“… 14 For instance, Li et al 15 observed a strong visible emission peak centered at about 609 nm in ZnO nanorods (15 nm in diameter) as a result of large quantities of defects, thus enabled the high ethanol response by the total surface depletion. Different morphologies of ZnO nanostructures such as thin films, 16 nanorods, 17 nanowires, 18 and nanoparticles 19 have been also investigated for gas sensor applications. In our previous study, 20 the gas sensing properties of ZnO nanorods, nanowires, and nanoparticles were systematically compared, where the nanoparticles exhibited higher ethanol sensitivity because of their smaller crystal size.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various metal oxides, zinc oxide (ZnO) is one of the widely studied and versatile material [7]. ZnO exhibits various properties such as hexagonal wurtzite structure with a direct and wide band gap energy (E g ) of 3.37 eV, large exciton binding energy (60 meV), colorless and transparent in visible region, non-toxic, cheap, thermally stable at room temperature, non-corrosive, and synthetic material [8][9][10][11][12][13], due to which it has been considered in wide range of applications, such as piezoelectric transducers, solar cell windows [14], ultraviolet (UV) detector, photocatalysis, gas sensors, photonics, spintronics, and antibacterial applications [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…This drawback has been addressed through multiplex ES (MES) techniques, demonstrating the simultaneous operation of hundreds of ES sources and a remarkable packing density exceeding 10 4 sources/cm 2 [33]. Thin films of MOS and conductive polymers have been prepared by ES of precursor solutions or nanoparticle suspensions for gas sensing applications [34][35][36][37][38][39]. Only recently ES has received attention for the preparation of gas sensors based on graphene [40,41].…”
Section: Introductionmentioning
confidence: 99%